2023
DOI: 10.22541/au.167769544.47033512/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual speech cues enhance neural speech tracking in right auditory cluster leading to improvement in speech in noise comprehension in older adults with hearing impairment

Abstract: Comprehending speech in noisy situations is difficult and suffers with aging, hearing loss, and cognitive decline. Using visual speech cues improves perception and comprehension of speech in noise (SiN) in older adults with hearing impairment. In the current study we investigated neurofunctional correlates (i.e., neural tracking of speech) of the visual enhancement effect in a naturalistic setting in which older adults with hearing impairment (N=67) listened to sentences in babble noise in audio-only and audio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…The study included 40 healthy retired participants (M age = 70, Range Age = 61-80, SD Age = 4.92, male = 20) who did not report pre-existing neurological or psychiatric conditions or any speech or language disorders. Sample size was based on previous work investigating behavioural and neural correlates of multimodal speech perception within the context of cognitive load (Frei et al, 2023;Frtusova & Phillips, 2016;Hjortkjaer et al, 2020;Schmitt et al, 2022). For the electrophysiological analysis three participants had to be excluded, due to constant noise over one of the two measurement sessions, leaving a total of 37 participants in the study.…”
Section: Samplementioning
confidence: 99%
“…The study included 40 healthy retired participants (M age = 70, Range Age = 61-80, SD Age = 4.92, male = 20) who did not report pre-existing neurological or psychiatric conditions or any speech or language disorders. Sample size was based on previous work investigating behavioural and neural correlates of multimodal speech perception within the context of cognitive load (Frei et al, 2023;Frtusova & Phillips, 2016;Hjortkjaer et al, 2020;Schmitt et al, 2022). For the electrophysiological analysis three participants had to be excluded, due to constant noise over one of the two measurement sessions, leaving a total of 37 participants in the study.…”
Section: Samplementioning
confidence: 99%
“…Further, Mégevand et al [ 19 ], in a study of the electrical activity of the human brain via implanted electrodes, found that visual speech cues in an audiovisual speech signal improved phase-tracking and reduced the amplitude of evoked responses to congruent auditory speech signals. Frei et al [ 20 ] also reported that visual speech cues increase neural tracking of the speech cues, particularly in the right auditory clusters, which subsequently results in better speech in noise comprehension in older adults with hearing loss. We speculate that after audiovisual speech stimulation, the improved capacity of the auditory cortex to track down the most critical features of speech, particularly in degraded listening conditions, does not vanish and is expected to persist for a longer period.…”
Section: Cognitive Mechanism Behind the Perceptual Doping Phenomenonmentioning
confidence: 99%